2015
DOI: 10.1103/physreva.92.033826
|View full text |Cite
|
Sign up to set email alerts
|

Spin squeezing of the non-Hermitian one-axis twisting model

Abstract: In the absence of decay, the conditional dynamics for an open system is often describable by a non-Hermitian Hamiltonian. This study investigates spin squeezing (SS) in non-Hermitian one-axis twisting (OAT) model. Somewhat surprisingly, SS close to the limit of Hermitian two-axis counter twisting (TACT) Hamiltonian is achievable for some parameters, which significantly improves upon the optimal value realizable by Hermitian OAT model. The drawback is like with all conditional schemes, it takes on average longe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
(60 reference statements)
2
17
0
Order By: Relevance
“…It is shown that the system amplifies the pattern of spin squeezing when the line width of the spin states are taken into account. Similar results have been found in [22]. The Authors of [22] have investigated the enhancement of spin squeezing in a non-Hermitian one-axis twisting model and its persistence in time [29].…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…It is shown that the system amplifies the pattern of spin squeezing when the line width of the spin states are taken into account. Similar results have been found in [22]. The Authors of [22] have investigated the enhancement of spin squeezing in a non-Hermitian one-axis twisting model and its persistence in time [29].…”
Section: Introductionsupporting
confidence: 74%
“…Similar results have been found in [22]. The Authors of [22] have investigated the enhancement of spin squeezing in a non-Hermitian one-axis twisting model and its persistence in time [29]. The Authors of [23,24] have reexamined the steady-state behaviours for a spin ensemble in diamond nanostructures by exerting a controllable microwave field.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…This points out the adverse effect of dephasing in keeping the quadrupolar spin in a squeezed state. On the other hand, recent studies on non-Hermitian TAC [38], and OAT [39] models have reported rather favorable squeezing conditions with respect to their Hermitian counterparts. The discrepancy may be caused by the fact that their models involved a dissipative channel, whereas we have a nondissipative phase-damping decoherence [28].…”
Section: Effect Of Zeeman Interaction and Dephasing On Steady Stamentioning
confidence: 99%
“…Even though TAC has superior squeezing characteristics [33], in spinor Bose-Einstein condensates it has only been indirectly realized by transforming OAT using pulse sequences, hence in this respect these can be classified as dynamical TAC [34][35][36][37]. Very recently it has been theoretically asserted that non-Hermitian OAT in the absence of decay can reach the squeezing limit of the Hermitian TAC model [38,39].…”
Section: Introductionmentioning
confidence: 99%